Contrasting results from molecular and pedigree‐based population diversity measures in captive zebra highlight challenges facing genetic management of zoo populations. Issue 1 (15th December 2016) - Ito, Hideyuki; Ogden, Rob; Langenhorst, Tanya; Inoue‐Murayama, Miho
Abstract : Zoo conservation breeding programs manage the retention of population genetic diversity through analysis of pedigree records. The range of demographic and genetic indices determined through pedigree analysis programs allows the conservation of diversity to be monitored relative to the particular founder population for a species. Such approaches are based on a number of well‐documented founder assumptions, however without knowledge of actual molecular genetic diversity there is a risk that pedigree‐based measures will be misinterpreted and population genetic diversity misunderstood. We examined the genetic diversity of the captive populations of Grevy's zebra, Hartmann's mountain zebra and plains zebra in Japan and the United Kingdom through analysis of mitochondrial DNA sequences. Very low nucleotide variability was observed in Grevy's zebra. The results were evaluated with respect to current and historic diversity in the wild, and indicate that low genetic diversity in the captive population is likely a result of low founder diversity, which in turn suggests relatively low wild genetic diversity prior to recent population declines. Comparison of molecular genetic diversity measures with analogous diversity indices generated from the studbook data for Grevy's zebra and Hartmann's mountain zebra show contrasting patterns, with Grevy's zebra displaying markedly less molecular diversity than mountain zebra, despite studbook analysis indicating that the Grevy's zebra population has substantially more founders, greater effective population size, lower mean kinship, and has suffered less loss of gene diversity. These findings emphasize the need to validate theoretical estimates of genetic diversity in captive breeding programs with empirical molecular genetic data. Zoo Biol. 36:87–94, 2017. © 2016 Wiley Periodicals, Inc.